Image enhancement using background brightness preserving histogram equalisation - Tan, T.L.; Sim, K.S.; Tso, C.P. (2012)
Histogram equalisation (HE) is widely used to enhance the image contrast but it tends to over-enhance the image background brightness. Improvement schemes have been introduced to reduce this defect of the conventional HE, but the over-enhancement of the background brightness is still obvious. A novel approach of nonlinear HE is presented, which is able to enhance the image contrast while preserving the background brightness for images with well-defined background brightness.